An Unusual Cause of Recurrent Pancreatitis: Duodenal Duplication Cyst. (1st April 2000) - Lad, Rameeta J; Fitzgerald, Peter; Jacobson, Kevan
Abstract : Intestinal duplications are rare anomalies that usually present in childhood.  Of these, duodenal duplications are among the most uncommon.  Although these usually present with obstructive symptoms or bleeding, pancreatitis may occur.  A case of duodenal duplication cyst causing recurrent pancreatitis in a 12-year-old girl is presented. The literature on duodenal duplications, and their epidemiology, embryology and pathophysiology is reviewed.